2012
DOI: 10.1016/j.jaci.2012.01.051
|View full text |Cite
|
Sign up to set email alerts
|

House dust bioactivities predict skin prick test reactivity for children with high risk of allergy

Abstract: Background Although evidence suggests that ambient exposures to endotoxin and other immunostimulants during early life influence allergic risk, efforts to understand this host-environment relationship have been hampered by a paucity of relevant assays. Objectives These investigations determined whether parameters of house dust extract (HDE) bioactivity were predictive of allergen skin prick test (SPT) reactivity for infants at high risk of allergy participating in the Cincinnati Childhood Allergy and Air Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…Thus, the previously demonstrated LPS-mediated augmentation of nasal responses in children with AR 40 might be caused by direct LPS-triggered responses in addition to classical antigen-IgE-mediated responses. Because LPS concentration that elicited sneezing in this study was within the range of endotoxin levels found in extracts from household dust, [25][26][27] endotoxin-elicited reactions might mediate rhinitis symptoms in 3-4). B and C, Number of sneezes at days 3 and 4 was counted for 10 minutes immediately after i.n.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Thus, the previously demonstrated LPS-mediated augmentation of nasal responses in children with AR 40 might be caused by direct LPS-triggered responses in addition to classical antigen-IgE-mediated responses. Because LPS concentration that elicited sneezing in this study was within the range of endotoxin levels found in extracts from household dust, [25][26][27] endotoxin-elicited reactions might mediate rhinitis symptoms in 3-4). B and C, Number of sneezes at days 3 and 4 was counted for 10 minutes immediately after i.n.…”
Section: Discussionmentioning
confidence: 73%
“…[17][18][19][20][21][22] These observations prompted us to investigate the causes and mechanisms of non-IgE-mediated type-1-hypersensitivity-like reactions. LPS, also known as endotoxin, is a component of the gramnegative bacterial cell wall and is a common contaminant in several allergens including household dust [23][24][25] and animal dander, 26,27 as well as ambient air pollutants. 28 Low-dose LPS is a well-known T H 2-inducing adjuvant in airway application models.…”
mentioning
confidence: 99%
“…For example, an association was seen between environmental tobacco smoke exposure and reduced dendritic cell interleukin 10 production during infancy (Gentile et al 2004 ). Further, exposure to urban air extract, fi ne and ultrafi ne particles or DEP all induced dendritic cell activation leading to production of IL-1β or TNF-α (Gentile et al 2004 ;Acciani et al 2013 ;Bonisch et al 2012 ;Kim et al 2012 ;Karle et al 2012 ;Myatt et al 2011 ;Bezemer et al 2011 ;Yoshida et al 2010 ;Williams et al 2008 ;de Haar et al 2008 ). A recent study in mice demonstrated that IL-1R, TLR4, and TLR2 predominant receptors on activated dendritic cells, elicited infl ammatory effects via MyD88 in response to wood or cow dung smoke derived PM suggesting that biomass fuel exposure elicits a persistent pulmonary infl ammation largely through activation of TLR and IL-1R pathways (Sussan et al 2014 ).…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…In addition to food allergens, indoor dust contains a mixture of environmental agents with immunostimulatory properties, including endotoxin, fungal‐derived polysaccharides, and proteases . These environmental agents can act as adjuvants in the respiratory tract and promote allergic sensitization to normally innocuous antigens in animal models .…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that the composition of environmental adjuvants in indoor dust can significantly influence sensitization and allergy development. Indeed, the bioactivity of indoor dust has been associated with aeroallergen sensitization in children at risk for allergy . We have previously shown that indoor dust extracts can programme lung cDCs to induce Th2 responses to inhaled antigens, resulting in the development of allergic airway inflammation upon subsequent inhalational allergen challenge .…”
Section: Introductionmentioning
confidence: 99%